Development of LM98, a Small‐Molecule TEAD Inhibitor Derived from Flufenamic Acid. (28th July 2021) - Mélin, Léa; Abdullayev, Shuay; Fnaiche, Ahmed; Vu, Victoria; González Suárez, Narjara; Zeng, Hong; Szewczyk, Magdalena M.; Li, Fengling; Senisterra, Guillermo; Allali‐Hassani, Abdellah; Chau, Irene; Dong, Aiping; et al.
Abstract: The YAP‐TEAD transcriptional complex is responsible for the expression of genes that regulate cancer cell growth and proliferation. Dysregulation of the Hippo pathway due to overexpression of TEAD has been reported in a wide range of cancers. Inhibition of TEAD represses the expression of associated genes, demonstrating the value of this transcription factor for the development of novel anti‐cancer therapies. We report herein the design, synthesis and biological evaluation of LM98, a flufenamic acid analogue. LM98 shows strong affinity to TEAD, inhibits its autopalmitoylation and reduces the YAP‐TEAD transcriptional activity. Binding of LM98 to TEAD was supported by 19 F‐NMR studies while co‐crystallization experiments confirmed that LM98 is anchored within the palmitic acid pocket of TEAD. LM98 reduces the expression of CTGF and Cyr61, inhibits MDA‐MB‐231 breast cancer cell migration and arrests cell cycling in the S phase during cell division. Abstract : Fusion chemistry : We report the design and development of LM98, a reversible TEAD inhibitor that originates from the fusion of flufenamic acid and palmitic acid. LM98 binds in the palmitic acid pocket of TEAD, preventing its autopalmitoylation and reducing the expression of associated genes. LM98 reduces TEAD activation, inhibits breast cancer cell migration and arrests cells in the S phase. Extensive SAR studies revealed new opportunities for future medicinal chemistry activities within this series.